One-Step Microwave Synthesis of Micro/Nanoscale LiFePO4/Graphene Cathode With High Performance for Lithium-Ion Batteries - Liu, Shulong; Yan, Ping; Li, Haibin; Zhang, Xiaobo; Sun, Wei (Frontiers in Chemistry, 2020)
In this study, micro/nanoscale LiFePO4/graphene composites are synthesized successfully using a one-step microwave heating method. One-step microwave heating can simplify the reduction step of graphene oxide and provide a convenient, economical, and effective method of preparing graphene composites. The structural analysis shows that LiFePO4/graphene has high phase purity and crystallinity. The morphological analysis shows that LiFePO4/graphene microspheres and micron blocks are composed of densely aggregated nanoparticles; the nanoparticle size can shorten the diffusion path of lithium ions and thus increase the lithium-ion diffusion rate. Additionally, the graphene sheets can provide a rapid transport path for electrons, thus increasing the electronic conductivity of the material. Furthermore, the nanoparticles being packed into the micron graphene sheets can ensure stability in the electrolyte during charging and discharging. Raman analysis reveals that the graphene has a high degree of graphitization. Electrochemical analysis shows that the LiFePO4/graphene has an excellent capacity, high rate performance, and cycle stability. The discharge capacities are 166.3, 156.1, 143.0, 132.4, and 120.9 mAh g−1 at rates of 0.1, 1, 3, 5, and 10 C, respectively. The superior electrochemical performance can be ascribed to the synergy of the shorter lithium-ion diffusion path achieved by LiFePO4 nanoparticles and the conductive networks of graphene.